2018
DOI: 10.1016/j.ymben.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Systematic overexpression study to find target enzymes enhancing production of terpenes in Synechocystis PCC 6803, using isoprene as a model compound

Abstract: Of the two natural metabolic pathways for making terpenoids, biotechnological utilization of the mevalonate (MVA) pathway has enabled commercial production of valuable compounds, while the more recently discovered but stoichiometrically more efficient methylerythritol phosphate (MEP) pathway is underdeveloped. We conducted a study on the overexpression of each enzyme in the MEP pathway in the unicellular cyanobacterium Synechocystis sp. PCC 6803, to identify potential targets for increasing flux towards terpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 67 publications
3
84
0
Order By: Relevance
“…However, recent experience has also shown that heterologous expression of eukaryotic plant and yeast genes occurs at low protein levels, regardless of the promoter used and mRNA levels achieved in the cyanobacterial cytosol (Formighieri and Melis, 2016). For example, plant terpene synthases could not be expressed well in cyanobacteria under the control of different strong endogenous and heterologous promoters (Formighieri and Melis, 2014;Englund et al, 2018). Heterologous expression in cyanobacteria of the isoprene synthase (Lindberg et al, 2010;Bentley and Melis, 2012), β-phellandrene synthase (Bentley et al, 2013), geranyl diphosphate (GPP) synthase from a higher plant origin (Bentley et al, 2014;Formighieri and Melis, 2017;Betterle and Melis, 2018), and the alcohol dehydrogenase (ADH1) gene from yeast (Chen and Melis, 2013), all showed low levels of recombinant protein expression, even under the control of strong endogenous (e.g., psbA2, rbcL, cpc) or strong heterologous promoters (e.g., Ptrc), and even after following a careful codonuse optimization of the target transgene (Lindberg et al, 2010;Bentley and Melis, 2012;Ungerer et al, 2012;Bentley et al, 2013;Chen and Melis, 2013;Formighieri and Melis, 2014;Englund et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent experience has also shown that heterologous expression of eukaryotic plant and yeast genes occurs at low protein levels, regardless of the promoter used and mRNA levels achieved in the cyanobacterial cytosol (Formighieri and Melis, 2016). For example, plant terpene synthases could not be expressed well in cyanobacteria under the control of different strong endogenous and heterologous promoters (Formighieri and Melis, 2014;Englund et al, 2018). Heterologous expression in cyanobacteria of the isoprene synthase (Lindberg et al, 2010;Bentley and Melis, 2012), β-phellandrene synthase (Bentley et al, 2013), geranyl diphosphate (GPP) synthase from a higher plant origin (Bentley et al, 2014;Formighieri and Melis, 2017;Betterle and Melis, 2018), and the alcohol dehydrogenase (ADH1) gene from yeast (Chen and Melis, 2013), all showed low levels of recombinant protein expression, even under the control of strong endogenous (e.g., psbA2, rbcL, cpc) or strong heterologous promoters (e.g., Ptrc), and even after following a careful codonuse optimization of the target transgene (Lindberg et al, 2010;Bentley and Melis, 2012;Ungerer et al, 2012;Bentley et al, 2013;Chen and Melis, 2013;Formighieri and Melis, 2014;Englund et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, plant terpene synthases could not be expressed well in cyanobacteria under the control of different strong endogenous and heterologous promoters (Formighieri and Melis, 2014;Englund et al, 2018). Heterologous expression in cyanobacteria of the isoprene synthase (Lindberg et al, 2010;Bentley and Melis, 2012), β-phellandrene synthase (Bentley et al, 2013), geranyl diphosphate (GPP) synthase from a higher plant origin (Bentley et al, 2014;Formighieri and Melis, 2017;Betterle and Melis, 2018), and the alcohol dehydrogenase (ADH1) gene from yeast (Chen and Melis, 2013), all showed low levels of recombinant protein expression, even under the control of strong endogenous (e.g., psbA2, rbcL, cpc) or strong heterologous promoters (e.g., Ptrc), and even after following a careful codonuse optimization of the target transgene (Lindberg et al, 2010;Bentley and Melis, 2012;Ungerer et al, 2012;Bentley et al, 2013;Chen and Melis, 2013;Formighieri and Melis, 2014;Englund et al, 2018). Similarly, only low levels of expression were reported for a chimeric complex of plant enzymes, including the ethylene synthase efe gene from Solanum lycopersicum (tomato) (Jindou et al, 2014;Xue and He, 2014), limonene synthase from Mentha spicata (spearmint) (Davies et al, 2014) and Picea sitchensis (Sitka spruce) (Halfmann et al, 2014b), the sesquiterpene farnesene and bisabolene synthases from Picea abies (Norway spruce) (Halfmann et al, 2014a) and Abies grandis (grand fir) (Davies et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene is produced endogenously by Synechocystis and other cyanobacteria as a precursor of other carotenoids used for photoprotection, but does not naturally accumulate ( Figure 2). To overproduce lycopene a pathway-encoding construct was designed using homologs of three native CDSs ( dxs , crtE , and crtB ) to boost pathway flux ( dxs is a known rate-limiting reaction in both E. coli 37,63,64 and cyanobacteria 14,15,65 ) and a heterologous CDS ( ctrI ), which provides a bacterial-type one-step desaturase to bypass the native photoautotroph-type two-step desaturase pathway 66 ( crtP and crtQ ) in the conversion of phytoene to lycopene ( Figure 2).…”
Section: Rationally-designed Individual Pathway Constructs Were Genetmentioning
confidence: 99%
“…Cyanobacteria have been genetically modified to synthesise a wide range of non-native compounds ranging from commodity chemicals and biofuels to high-value products, including alcohols [5][6][7][8] , organic acids [8][9][10][11] , diols 12,13 , terpenoids [14][15][16][17][18][19][20] , sugars [21][22][23] and many others [24][25][26][27][28][29] . However, production using cyanobacteria is not yet commercially competitive [30][31][32] with production by petrochemical or conventional heterotrophic biotechnology approaches, both of which benefit from the current low economic costs of using fossil carbon and emitting CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…PCC 6803 (from here: Synechocystis) resulted in 2.5-fold higher isoprene yields [12]. Likewise, numerous rational design studies targeting selected bottleneck steps within the MEP pathway as well as selected steps of upstream carbon fluxes lent support to this concept [8,9,[13][14][15][16][17][18][19]. Further strategies sought to challenge the problem of inherently weak terpene synthase activities by increasing cellular enzyme titers, concurrently pushing carbon flux towards the heterologous metabolic sink.…”
Section: Introductionmentioning
confidence: 99%